2020
DOI: 10.1002/ehf2.12658
|View full text |Cite
|
Sign up to set email alerts
|

Monozygotic twins with myocarditis and a novel likely pathogenic desmoplakin gene variant

Abstract: Myocarditis most often affects otherwise healthy athletes and is one of the leading causes of sudden death in children and young adults. Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a genetically determined heart muscle disorder with increased risk for paroxysmal ventricular arrhythmias and sudden cardiac death. The clinical picture of myocarditis and ARVC may overlap during the early stages of cardiomyopathy, which may lead to misdiagnosis. In the literature, we found several cases that presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The full-text screening of these articles led to the exclusion of 56 studies due to their compliance with the inclusion/ exclusion criteria. The remaining 31 articles were considered eligible for this review [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] A PRISMA flow diagram depicts the flow of information through the different literature review phases ( Figure 1 ). Our inclusion criteria, with regard to the presence of detailed patients’ clinical features, led to the exclusion of several publications reporting a significant number of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The full-text screening of these articles led to the exclusion of 56 studies due to their compliance with the inclusion/ exclusion criteria. The remaining 31 articles were considered eligible for this review [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] A PRISMA flow diagram depicts the flow of information through the different literature review phases ( Figure 1 ). Our inclusion criteria, with regard to the presence of detailed patients’ clinical features, led to the exclusion of several publications reporting a significant number of subjects.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, only two patients have been reported to have desmoglein-2 mutation, presenting with ARVC and concomitant biventricular myocarditis (5,10). It seems that the clinical presentation, including LV involvement, cannot be explained simply by the type of gene mutation (10), although desmoplakin mutation carriers mostly develop LV involvement (2,5,6).…”
Section: Arvc and Desmosomal Gene Mutationsmentioning
confidence: 95%
“…Recently, myocardial inflammation has been considered to be involved in the pathogenesis of ARVC (5). Several case reports have described patients with ARVC initially presenting with clinical acute or recurrent myocarditis and predominantly showing left ventricular abnormalities (1,5,6). However, there have been a few reports of cases presenting with right ventricular abnormalities with chronic myocarditis in advanced-stage ARVC (7).…”
Section: Introductionmentioning
confidence: 99%
“…The first study establishing a link between genetics and viral susceptibility in ACM patients showed that family members carrying the same causative rare variant in the DSP gene seemed to be particularly vulnerable to develop viral myocarditis (116). Recently, some reports have also suggested the relation between DSP mutations and a family history of recurrent myocarditis (117,118). In another study, genetic analysis on three cases of myocarditis-related SCD and their family members revealed the presence of rare novel variants predicted as deleterious and potentially pathogenic in ACM-related genes (PKP2, DSP DSC2, and TTN) (115), also including DSP as a crucial gene involved.…”
Section: Link Between Genetic Defect In Acm and Viral Infection Susceptibility: A Potential Genetic Predisposition?mentioning
confidence: 99%